Elucidating the Role of HIF-1α/YAP Signaling Pathway in Regulating Inflammation in Human Periodontal Stem Cells: An in vitro Study - Zhao HW; Liu ST; Wang XJ; Zhang XM; Ma X (Journal of Inflammation Research)
Hui-Wei Zhao,1 Shu-Tai Liu,2 Xiang-Jin Wang,1 Xue-Mei Zhang,1 Xiang Ma1 1Department of Periodontology, The Affiliated Yantai Stomatological Hospital, Binzhou Medical University, Yantai, 264000, People’s Republic of China; 2Department of Periodontology, Shenzhen Stomatology Hospital, Shenzhen, 518000, People’s Republic of ChinaCorrespondence: Xiang Ma, Department of Periodontology, The Affiliated Yantai Stomatological Hospital, Binzhou Medical University, 148 North Road, YanTai, People’s Republic of China, Email MaXiang900218@163.comBackground and Objective: Periodontitis is a chronic inflammatory disease caused by dental plaque accumulation, leading to damage of periodontal tissues and potential tooth loss. Understanding the mechanisms of periodontitis, particularly the role of hypoxia in inflammation, is critical for identifying novel therapeutic strategies. This study investigated the effects of the prolyl hydroxylase (PHD) inhibitor DMOG on pro-inflammatory cytokine expression in human periodontal ligament stem cells (hPDLSCs) and examined the involvement of the HIF-1α/YAP signaling path ay in modulating inflammation.Materials and Methods: hPDLSCs were cultured and treated with lipopolysaccharide (LPS) to induce inflammation, followed by DMOG treatment. Cell proliferation was assessed using the CCK-8 assay, while ELISA and RT-qPCR evaluated the expression levels of HIF-1α, IL-1β, TNF-α, and YAP. YAP expression was knocked down using siRNA transfection to examine its effects on inflammatory cytokines.Results: DMOG significantly increased HIF-1α expression while reducing IL-1β and TNF-α levels in LPS-treated hPDLSCs. 0.1 mmol/L DMOG inhibited cell proliferation after 72 hours (P < 0.001). ELISA results showed that HIF-1α concentrations in the LPS + DMOG group were significantly higher than in the LPS group (P < 0.01), while IL-1β and TNF-α levels were significantly reduced (P < 0.01). RT-qPCR confirmed these trends, showing reduced mRNA levels of IL-1β and TNF-α and increased YAP expression in the LPS + DMOG group (P < 0.0001). YAP knockdown via siRNA transfection reversed these effects, increasing IL-1β and TNF-α levels (P < 0.01) while significantly reducing HIF-1α expression (P < 0.05).Conclusion: This study demonstrated that DMOG reduces inflammatory cytokine expression in hPDLSCs by stabilizing HIF-1α and activating the YAP signaling pathway. These findings provide a mechanistic basis for targeting the HIF-1α/YAP axis to control periodontal inflammation and support the potential of PHD inhibitors as therapeutic agents for periodontitis.Keywords: periodontitis, HIF-1α, YAP, DMOG, inflammation